Acute exposure of minimally oxLDL elicits survival responses by downregulating the mediators of NLRP3 inflammasome in cultured RAW 264.7 macrophages. (22nd August 2022) - Thankam, Finosh G; Khwaja, Bisma; Nguyen, Megan; Ahsan, Osama; Agrawal, Devendra K
Abstract: Lipid burden in macrophages driven by oxidized low-density lipoprotein (oxLDL) accelerates the foam cell formation and the activation of sterile inflammatory responses aggravating the atherosclerosis. However, there is limited information on the mediators and the pathways involved in the possible survival responses, especially at the initial phase, by lipid burden in macrophage cells on encountering oxLDL. The present study was designed to assess the expression status of major mediators involved in the NLRP3 inflammasome pathway of sterile inflammation and the cellular responses in oxLDL-challenged cultured RAW 264.7 macrophage cells. OxLDL-treated RAW 264.7 macrophage cells displayed a decreased expression of the key sterile inflammatory mediators, TLR4, TLR2, ASC, NLRP3 and IL-18 at protein and transcript levels; however, they displayed increased level of IL-1β, RAGE and TREM1 at protein level. Biological responses including lipid uptake, lipid peroxidation, cellular hypertrophy, mitochondrial density and mitochondrial membrane potential were significantly increased in oxLDL-treated macrophages. Moreover, superoxide production was significantly decreased in the oxLDL-treated macrophages compared to the control. Overall, the findings revealed the expression status of key sterile mediators and the macrophage response during the initial phase of oxLDL exposure tend towards the prevention of inflammation. Further understanding would open novel translational opportunities in the management of atherosclerosis. Graphical Abstract: